A systematic framework for assessing the applicability of reactive distillation for quaternary mixtures using a mapping method. (8th May 2020) - Muthia, Rahma; Jobson, Megan; Kiss, Anton A.
Highlights: New systematic framework for evaluating the applicability of reactive distillation. Mapping method is used to screen reactive distillation designs in non-ideal systems. Case studies covering non-ideal quaternary systems with various boiling point ranking. Abstract: Reactive distillation (RD) is a useful process intensification technique used in the chemical process industries as it offers important advantages such as energy and cost savings, relative to conventional technologies. However, industrial application of RD is still limited by the complexity of designing and understanding such a complex process. While simple, robust shortcut design methods that require only basic information (such as the relative volatility of components) exist for conventional distillation, such methods for evaluating the applicability of RD are not yet established. This work fills this gap by presenting a new systematic framework for assessing the RD applicability based on a mapping method. The method enables RD designs to be screened using only relative volatilities and chemical equilibrium constant as input data. The evaluation focuses on reactions involving four components (A + B ⇌ C + D) with various boiling point orders, which are of most industrial importance. The proposed systematic framework is validated through its application to five case studies, (trans-)esterifications presenting various separation challenges due to the formation of azeotropes. This novel approach offers a valuable aid for engineers in taking an educated go/no-go decision in the very initial stages of conceptual design, before performing any rigorous simulations of RD flowsheets.